Book reviews [International Journal of Emotional Education, 17(1)] - Helen Cowie (International Journal of Emotional Education)
In this issue we take two different perspectives on the recently published monograph by Paul Downes, Towards a concentric spatial psychology for social and emotional education: Beyond the interlocking spatial pillars of modernism. Because the book offers a complex new way of looking at concentric spatial psychology and how this model might apply to contexts of social and emotional education, we invited two reviewers, Dr Daniel Stolfi, an anthropologist and psychotherapist, and Prof Paul Bartolo, a psychologist and educator with a special interest in social and emotional education, to give their different perspectives on the book. The outcome is two fascinating interpretations of the model, illustrated in unique ways that spark the reader’s interest. We end with a review by Prof. Gillean McLuskey of the recent book by Joan Mowat, entitled Building community to create equitable, inclusive and compassionate schools through relational approaches. This is a topic dear to the hearts of most readers of IJEE. The book integrates practical strategies with policy-making and theoretical insights. As you will see, true acceptance of diversity as well as commitment to equity and inclusiveness permeate the three reviews.